Innovation under the Unique Pressures of Energy Transition: Can CSR Strategy Buffer ESG Controversies in EU Firms - Aljawarneh, Nader Mohammad; Al Daabseh, Tariq Khairo Issa; Alomari, Khaled Abdel Kader; Alazzam, Farouq Ahmad Faleh; Alqudah, Mohammad Zakaria; Alslaibi, Naji Anton; Abu Huson, Yazan; Almarashdi, Feras; Al Momani, Mohammad Ahmad Hamad (International Journal of Energy Economics and Policy, 2026)
This study addresses issues related to Environmental, Social, and Governance (ESG) activities in the energy industry—namely, carbon emissions disputes, nuclear safety concerns, divestments in fossil fuels and bottlenecks in renewable transition—that affect carbon emissions disputes, nuclear safety concerns, divestments in fossil fuels and bottlenecks in renewable transition on firms' environmental innovation performance. It also investigates whether CSR strategy attenuates these effects, with a focus on industry-specific innovations such as carbon capture, smart grids, and renewables technologies. The study utilizes an unbalanced panel of 233 firm-year observations for European Union energy firms over the period 2015–2023, and uses fixed effects (FE), high-dimensional fixed effects (HDFE), as well as system GMM estimations to control for heterogeneity and endogeneity. The finding revealed that ESG controversies significantly curb environmental innovation at energy firms due to reputational harm, regulatory pressures, and reallocation of resources. Governance attributes, including board size, gender diversity, and leverage, encourage innovation, while the impact of audit committee independence and expertise is mixed. The CSR strategy does not have a significant impact on the controversy–innovation relationship, suggesting that the CSR endeavor alone is not sufficient to safeguard the ability to innovate in the energy industry. The results illustrate that ESG is a bottleneck for carbon neutrality and energy transition. Policymakers and business leaders need to embed ESG risk management in innovation strategies. This research contributes to insights into energy-ESG risks and their link to technology development necessary to achieve a sustainable transition.